Effect of piscivorous and omnivorous colonial birds' activity on structure, abundance and diversity of soil free-living nematodes. Preliminary results from a study of the impact of avifauna on soil biota in Israel's Mediterranean Coastal Plain. (December 2019) - Pen-Mouratov, Stanislav; Dayan, Tamar
Highlights: Soil biota is affected by activity of piscivorous and omnivorous colonial birds. Bird activity affects the structure of soil free-living nematode communities. Different colonial birds can have stimulatory or inhibitory impacts on soil biota. Abstract: The soil biota, including soil microorganisms and free-living nematodes, was investigated in the nesting and roosting habitats of the following piscivorous and omnivorous colonial birds: black kite ( Milvus migrans ), great cormorant ( Phalacrocorax carbo ), black-crowned night heron ( Nycticorax nycticorax ) and little egret ( Egretta garzetta ), in Israel's Mediterranean region. Abiotic variables, abundance, trophic structure, sex ratio and genus diversity of soil free-living nematodes, and total abundance of bacteria and fungi, were measured during the hottest period of 2016. The impact of the birds' activity on the soil biota was most notable in the upper soil layer and weaker in the lower soil layer. Soil properties such as alkalinity (pH) and conductivity, along with contents of ammonium, nitrate and phosphorus were found to be among the main drivers influencing prey–predator relationships in the observed soil habitat by altering the predation success of soil free-living nematodes. The observed nematode species were affected by the birds' nesting and roosting activity, as reflected by an increasing proportion of common nematodes and the disappearance of rare species in the colonial birds' habitats. The applied ecological indices showed that the different species of colonial birds can have different (stimulatory or inhibitory) impacts on the abundance and diversity of the soil biota, affecting the structure of soil free-living nematodes at the generic, trophic and sexual levels. Moreover, the soil ecosystem in the area of bird activity had a less complex food web, but with higher concentrations of nutrients than the uninhabited control area.